KETELADANAN ORANG TUA DALAM INTERAKSI LINTAS AGAMA DAN IMPLIKASINYA TERHADAP TINGKAH LAKU ANAK PERSPEKTIF PENDIDIKAN ISLAM - Shaumy Imani Istiqomah; Mira Mareta; Maimun Maimun; Hilmiati Hilmiati; M. Sobry (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT This study was motivated by the importance of parental role modeling in shaping children’s tolerant behavior within a pluralistic society. The study aimed to analyze parents’ exemplary attitudes in interfaith interactions and their implications for children’s behavior from the perspective of Islamic education. This research employed a descriptive qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving Muslim families living alongside non-Muslim communities. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that parents’ exemplary behavior in building harmonious relationships with non-Muslims had a positive influence on children’s behavioral development. Children tended to demonstrate tolerant attitudes, politeness, respect for differences, and the ability to establish positive social relationships within their environment. In the perspective of Islamic education, these behaviors are aligned with the values of tasamuh, ukhuwah insaniyah, and hablum minannas, which emphasize the importance of noble character in social life. In addition, the study found that children who were consistently exposed to positive interfaith interactions within the family environment developed stronger social adaptability and greater openness toward diversity. The findings also indicate that family-based character education through parental role modeling can serve as an effective strategy for fostering social harmony and strengthening inclusive attitudes among children in multicultural communities. This study confirms that parental role modeling serves as an effective medium of social education in shaping children’s tolerant behavior in a pluralistic society. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya keteladanan orang tua dalam membentuk perilaku toleran anak di tengah masyarakat plural. Penelitian bertujuan menganalisis keteladanan orang tua dalam interaksi lintas agama serta implikasinya terhadap tingkah laku anak dalam perspektif pendidikan Islam. Penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian lapangan (field research). Data diperoleh melalui observasi, wawancara, dan dokumentasi terhadap keluarga Muslim yang hidup berdampingan dengan masyarakat non-Muslim. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa keteladanan orang tua dalam membangun hubungan harmonis dengan non-Muslim memberikan pengaruh positif terhadap pembentukan perilaku anak. Anak cenderung menunjukkan sikap toleran, santun, menghargai perbedaan, serta mampu menjalin hubungan sosial yang baik dengan lingkungan sekitar. Dalam perspektif pendidikan Islam, perilaku tersebut sejalan dengan nilai tasamuh, ukhuwah insaniyah, dan hablum minannas yang menekankan pentingnya akhlakul karimah dalam kehidupan bermasyarakat. Selain itu, pembiasaan interaksi sosial yang harmonis dalam keluarga turut memperkuat kemampuan anak dalam beradaptasi dengan keberagaman sosial di lingkungannya. Proses keteladanan yang dilakukan secara konsisten juga membentuk kesadaran anak untuk menjunjung sikap saling menghormati dan hidup damai di tengah perbedaan keyakinan. Penelitian ini menegaskan bahwa keteladanan orang tua menjadi media pendidikan sosial yang efektif dalam membentuk perilaku toleran anak di masyarakat plural.